2007
DOI: 10.1002/mar.20197
|View full text |Cite
|
Sign up to set email alerts
|

Measuring values using best‐worst scaling: The LOV example

Abstract: The paper discusses the way that values have been measured and suggests an alternative way to collect values data. A recently developed approach, termed Best Worst Scaling, developed by Louviere and his colleagues, offers an opportunity to collect such data in a way that may produce more desirable values estimates. Kahle's (1983) List of Values, which has been widely employed in consumer research, was used to examine differences between the new approach and traditional ratings and rankings approaches. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 47 publications
3
100
0
4
Order By: Relevance
“…Furthermore, efficient estimates can be obtained when repeated choices are made by the same respondent, which is the case in this present study [14]. Finally, the best worst approach is gaining more popularity as a better alternative to the rating system and measuring value [15]. Therefore, the best worst approach reported above fit well in this present study related to consumers' preferences for quality and safety attributes of milk products.…”
Section: Methodssupporting
confidence: 55%
“…Furthermore, efficient estimates can be obtained when repeated choices are made by the same respondent, which is the case in this present study [14]. Finally, the best worst approach is gaining more popularity as a better alternative to the rating system and measuring value [15]. Therefore, the best worst approach reported above fit well in this present study related to consumers' preferences for quality and safety attributes of milk products.…”
Section: Methodssupporting
confidence: 55%
“…For example, Lee et al (2007Lee et al ( , 2008 showed that they could reformulate and replicate the Schwartz value scale using an experimental best-worst design structure; but, they did not ask the more fundamental question of whether the value structure proposed by Schwartz could be recreated if rebuilt from scratch, nor whether that structure was more predictively valid than some outer grounded alternative. In this regard, we need more grounded research that works to create alternative cultural structures and dimensions that we can subject to testing and formal modeling.…”
Section: Rethinking Culture Methodologicallymentioning
confidence: 99%
“…The values relate to the major roles in life, such as marriage, parenting, work, leisure, and consumption (Kahle, Beatty, & Homer, 1986) and consist of eight items: sense of belonging, warm relationships with others, selffulfillment, being well respected, fun and enjoyment of life, security, self-respect, and a sense of accomplishment. The scoring system used here was selected from a number of alternatives (Kahle & Kennedy, 1988;Kennedy, Best, & Kahle, 1988;Lee, Soutar, & Louviere, 2007) and required respondents to rate each value on a 9-point scale of importance.…”
Section: Methodsmentioning
confidence: 99%